ASSOCIATION OF CORRECTED QT INTERVAL WITH MICROVASCULAR COMPLICATIONS OF TYPE 2 DIABETES MELLITUS - Dr. Tejashree Pasumarthy; Dr. Fareeha Afreen; Dr. Pooja Rajesh Naik; Dr. Seetha VSR Prashanthi; Dr. Javeria Afshan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background and Objectives: There is a rising incidence of type 2 diabetes mellitus, and hyperglycaemia is known to cause microvascular complications and macrovascular complications like ischemic heart disease and sudden cardiac death. Each microvascular complication is an independent risk factor for sudden cardiac death. QT interval, corrected for heart rate, is a simple electrocardiogram (ECG)-based method indicating cardiac repolarization abnormality. Prolonged QTc lowers the threshold for life-threatening cardiac arrhythmias. The present study examines the association of QTc interval with microvascular complications in diabetes mellitus.Methods: A cross-sectional study was conducted from January 2020 to June 2021. A total of 117 patients with type 2 diabetes mellitus were enrolled after obtaining informed consent. All participants underwent clinical examination and laboratory investigations. Statistical analysis was performed to correlate the QTc interval with microvascular complications using SPSS software. Unpaired t-test and chi-square test were applied.Results: Out of 117 patients, 45 were female and 72 were male. Prolonged QT interval was found in 12% of participants (p < 0.001). There was no significant difference in age, duration of diabetes, or glycemic control between those with and without prolonged QT. QT prolongation was significantly associated with diabetic retinopathy (20.3%), nephropathy (22.9%), and neuropathy (29.0%).Conclusion: There is a significant association between QT interval prolongation and the severity and multiplicity of diabetic microvascular complications. QTc interval serves as a simple and cost-effective method for early detection of cardiovascular risk in patients with type 2 diabetes mellitus.